Analysis of the Grammatical Content in some Selected Senior Secondary English Language Textbooks in Oyo State (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This study analyses the grammatical content in some selected senior secondary English Language textbooks (Intensive English II and Effective English II) in Oyo State. The study adopts the survey research design. Fifty teachers of English Language were randomly selected from senior secondary schools in Oyo State. The research instrument used for data collection was Grammatical Content Adequacy Scale (r=0.81). Data collected were analysed using descriptive statistics of percentage scores, mean, standard deviation and inferential statistics of t-test. The results show that the grammatical contents of the two recommended English language textbooks used in senior secondary school II were high. The findings also revealed that the two textbooks were not significantly different (t= -2.078; df=2; p>.05).  Based on the findings of this study, the paper recommends that government and stakeholders in textbook selection should always consider the grammatical content of textbooks as well as the age of a learner determines the method, technique and the level of language to be used in the classroom. In addition, because background knowledge of a text is very essential. Writers should therefore include passages that are familiar to students when constructing passages.
Keywords: English Language; English Grammar; Grammatical Content; Textbooks; English Language Textbooks